Candida albicans and Early Childhood Caries: A Systematic Review and Meta-Analysis - Xiao, Jin; Huang, Xuelian; Alkhers, Naemah; Alzamil, Hassan; Alzoubi, Sari; Wu, Tong Tong; Castillo, Daniel A; Campbell, Frank; Davis, Joseph; Herzog, Karli; Billings, Ronald; Kopycka-Kedzierawski, Dorota T; et al. (Caries research, 2018)
Oral Candida albicans has been detected in children with early childhood caries (ECC) and has demonstrated cariogenic traits in animal models of the disease. Conversely, other studies found no positive correlation between C. albicans and caries experience in children, while suggesting it may have protective effects as a commensal organism. Thus, this study aimed to examine whether oral C. albicans is associated with ECC. Seven electronic databases were searched. The data from eligible studies were extracted, and the risk of bias was evaluated. A fixed effects model (Mantel-Haenszel estimate) was used for meta-analysis, and the summary effect measure was calculated by odds ratio (OR) and 95% confidence interval (CI). Fifteen cross-sectional studies were included for the qualitative assessment and 9 studies for meta-analysis. Twelve studies revealed higher oral C. albicans prevalence in ECC children than in caries-free children, while 2 studies indicated an equivalent prevalence. A pooled estimate, with OR = 6.51 and 95% CI = 4.94-8.57, indicated a significantly higher ECC experience in children with oral C. albicans than those without C. albicans (p < 0.01). The odds of experiencing ECC in children with C. albicans versus children without C. albicans were 5.26 for salivary, 6.69 for plaque, and 6.3 for oral swab samples. This systematic review indicates that children with oral C. albicans have >5 times higher odds of having ECC compared to those without C. albicans. Further prospective cohort studies are needed to determine whether C. albicans could be a risk factor for ECC, and whether it is dependent on different sample sources (saliva/plaque).